Kualitas semen segar dan recovery rate sapi bali pada musim yang berbeda - Siti Aisah; Nurul Isnaini; Sri Wahyuningsih (Faculty of Animal Science, Universitas Brawijaya, 2017)
This research was conducted at the Center of Artificial Insemination (BBIB)Singosari , Malang, East Java. The purpose of this research was to determinethe parameters of fresh semen quality including volume, pH, individual motilityand concentration of frozen semen production and recovery rate of Bali bullsin different seasons. The material used were fresh semen of 14 heads of Bali’sbull in 3, 5, 6, 10, and 11 years and secondary data from November 2015 toSeptember 2016 at BBIB Singosari. The method used in this research was casestudy and the data were analyzed descriptively. The results showed that thehighest volume semen Bali bull in summer was 6.05±1.50 ml. The pH in rainyseason and summer were 6.5±0.07. Semen of Bali’s bull dominated by the white-milk color. The highest of color (white-milk), individual motility, concentrationand total of frozen semen production were at summer in September. The average ofcolor, individual motility, concentration and total of fozen semen productionwere 89%±0.10, 66.98 ± 0.05%, 1159.25 ± 211.28 million/ml and 22682 ± 707.95straw. Post thawing Motility (PTM) and RR value were 45.28 ± 0.02%; 66.79± 0.05semen of Bali’s bull highest at summer in August. The conclusion showed thedifferences of season will affect to volume, color, individual motility,concentration, PTM, the value of RR and production of frozen semen Bali bull,but it is not effect for pH semen.